APPLICATION OF POSITIVE MATRIX FACTORIZATION IN SOURCE APPORTIONMENT OF PARTICULATE POLLUTANTS IN BANDUNG CITY - DWI MAULIADI (NIM 25305019); Pembimbing: Ir. Puji Lestari, Ph.D., YANDHINUR
A Receptor Model method of Positive Matrix Factorization (PMF) was used to identify the emission sources of fine and coarse particulates in Bandung city. The data were collected using Dichotomous Sampler to collect samples which will be analyzed for its carbon and metal contents and MiniVol to collect samples which will be analyzed for its cation-anion elements. The species analyzed in this study are Na, Mg, Al, Si, K, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd, Sb, Pb, Li, Mo, Cl-, NO3-, SO4-, Na+, NH4+, K+, Mg 2-, Ca 2+. This study took place in Dago Pakar during wet and dry season. The result show that during wet season, fine particles were contributed by Secondary Aerosol (NH4)2SO4 (14%), secondary aerosol NH4NO3 (12%), Volcanic dust (6%), soil dust (10%), biomass burning (13%), lime dust (10%), diesel vehicle (17%), motorcycle (9%), and gasoline vehicle (9%), while coarse particles were contributed by lime dust (20%), soil dust (20%), industry (15%), volcanic dust (4%), construction dust (15%) and sea spray (26%). During dry season, fine particles were contributed by secondary aerosol (NH4)2SO4 (25%), diesel engine vehicle (12%), biomass burning (16%), gasoline vehicle (3%), aged sea salt (13%), electroplating industry (24%) and motorcycle (7%), while coarse particles were contributed by sea spray (14%), ferrous industry (23%), cement industry (11%), volcanic dust (25%), sil dust (15%), and aged sea salt (3%).